2011
DOI: 10.1093/ndt/gfr578
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular and renal outcome in recipients of kidney grafts from living donors: role of aortic stiffness

Abstract: Donor large artery stiffness may predict recipient CV and graft outcome. This finding demonstrates the tight link that exists between the vascular system and the kidneys and suggests that donor contribution to recipient outcome goes beyond simple parameters like age, gender and even familial or non-familial donor type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 23 publications
0
12
0
Order By: Relevance
“…Normally, the link between the kidney and the large arterial system is tight and a recent study [13] has demonstrated that donor contribution to recipient outcome may go beyond age and gender, as previously suggested [30]. Furthermore, in the general population at large, and in the renal population in particular, there is a clear cross talk between the large arterial system and the kidney that is further amplified by age, which reflects the cumulative duration of the vascular-renal interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Normally, the link between the kidney and the large arterial system is tight and a recent study [13] has demonstrated that donor contribution to recipient outcome may go beyond age and gender, as previously suggested [30]. Furthermore, in the general population at large, and in the renal population in particular, there is a clear cross talk between the large arterial system and the kidney that is further amplified by age, which reflects the cumulative duration of the vascular-renal interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Factors predicting or associated with graft function decline were mostly related to the recipient, and the only identified donor factors were age and gender. To our knowledge, other donor-related parameters, such as arterial function and renal function were not thoroughly evaluated in relation to graft function progression over time in the recipient despite recent findings linking recipient arterial stiffness to kidney function in the renal transplant population [10,11,12,13], and more specifically, donor aortic pulse wave velocity (PWV) with late post-transplant occurrence of cardiovascular events and graft failure [13]. …”
Section: Introductionmentioning
confidence: 99%
“…Consistent with prior literature in the general and HD populations, a history of CV events was the most significant correlate of future CV events during the 12month follow-up period. [20][21][22][23] Despite the major risk levied by the history of prior CV events, the change in cfPWV during 2 years retained significant association with the incidence of CV events. This association was consistently observed for both the time span between the two cfPWV measurements and the 1-year followup period, even following the adjustment for major CV risk factors including age, sex, active smoking, BP parameters, diabetes mellitus, hypercholesterolemia, and history of CV events.…”
Section: Discussionmentioning
confidence: 96%
“…Consistent with prior literature in the general and HD populations, a history of CV events was the most significant correlate of future CV events during the 12‐month follow‐up period . Despite the major risk levied by the history of prior CV events, the change in cfPWV during 2 years retained significant association with the incidence of CV events.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have noted that BNP acts on the GC-A receptor of neighboring endothelial cells and possibly participates in coordinating endothelial regeneration/hypertrophy and the accompanying angiogenesis 3) . Donor large artery stiffness predicts a renal transplant recipient's cardiovascular and graft outcomes 4) . Aortic stiffness and increased wave reflections are independent predictors of cardiovascular events in renal transplant recipients 5) .…”
Section: Discussionmentioning
confidence: 99%